DESIGN OF A WEBSITE-BASED FRUIT SEED SALES INFORMATION SYSTEM - Muhammad Nurhidayat; Arif Senja Fitrani; Ika Ratna Indra Astutik; Sumarno Sumarno (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the “Design of a Website-Based Fruit Seed Information System” in Tulangan District, Sidoarjo Regency, as a technological innovation to enhance agricultural management within the context of globalization and the Industrial Revolution 4.0. Method: The research employed a developmental and testing approach, where 10 users participated in system trials to assess usability, response time, and data accuracy. The system utilized a MySQL database and was evaluated based on service speed, data input success, and user satisfaction. Results: The findings revealed that the average service time was reduced to 5 minutes—significantly faster than manual transactions—with 80% of users successfully entering data and 90% expressing satisfaction with the system’s ease of use. The average seller response time ranged between 2–5 minutes, and all transactions were encrypted to ensure data security. Novelty: This study presents an innovative integration of digital technology into the agricultural sector, demonstrating how a web-based system can streamline seed sales, promote digital literacy among farmers, and improve agricultural productivity through efficient information management.